Identifikasi Sumber Kepuasan Kerja Dan Pengaruhnya Terhadap Kinerja Petugas Unit Pengelola Kegiatan PNPM Mandiri Perdesaan Di Kabupaten Lumajang - Kasno Kasno; Hesti Budiwati (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2016)
This study aims to identify the source of job satisfaction and its effect partially or simultaneously on the performance of Activity Management Unit officer PNPM in Lumajang. Sources of job satisfaction were used in this study refers to the dimensions of job satisfaction include: (1) employment, (2) the conditions of employment, (3) salary, (4) co-workers, (5 ) the safety and security of employment , (6 ) supervision. Sources of job satisfaction will be tested influence either partially or simultaneously on performance. The population in this study is the Project Management Unit officer PNPM in Lumajang , with the number of samples taken as respondents by 37 respondents. Data were analyzed using multiple linear regression analysis. The results showed that only partially work variables that significantly influence the performance , while the variable conditions of employment , salary , co-workers, K3 and supervision no significant effect on performance. Simultaneously source of job satisfaction have a significant effect on performance. The coefficient of determination shows that the performance is influenced by 48.4 % performance can be explained by the variable of work , working conditions , salary , co-workers , occupational health and safety monitoring, while the remaining 51.6 % performance is influenced by other variables. Further research is expected to contribute in the development of management science studies , especially the management of human resources , so it can be a reference for similar research and advanced research